Wings - Zamecnik, J. S. 1872-1953 (Eureka, 2014)
"Two young men, one rich, one middle class, are in love with the same woman, but must leave her behind when they become fighter pilots in World War I." [imdb.com]
Original: USA 1927
s/w, getönt, Bildformat 1.33:1, 1080p AVC encode (Blu-ray), progressive encode (DVD)
Keywords: DVD-Video